2022
DOI: 10.1001/jamadermatol.2022.0364
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Persistence of First-line Biologics for Patients With Psoriasis and Psoriatic Arthritis in the French Health Insurance Database

Abstract: IMPORTANCETreatment options for psoriasis (PsO) and psoriatic arthritis (PsA) have evolved significantly throughout the era of biologics. Clinical trials are inadequate to assess the relative long-term efficacy of biologics and are often insufficient regarding safety.OBJECTIVES To assess the long-term persistence of different biologic classes to treat PsO and PsA. DESIGN, SETTING, AND PARTICIPANTSThis nationwide cohort study involved the administrative health care database of the French health insurance scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…Given that the recommended maintenance dosing interval for ustekinumab is every 12 weeks (84 days), a 45-days gap may not be sufficient to assess discontinuation of ustekinumab. The study that used a 60-days treatment gap reported results that are consistent with our own; 1-year persistence in patients with psoriasis was 81.1% for ustekinumab versus 72.9% for adalimumab and 69.7% for etanercept ( Pina Vegas et al, 2022 ). Over the entire 3-years observation period ustekinumab was associated with higher persistence than all tumor necrosis factor inhibitors (HR 0.76, 95% CI 0.72–0.80) ( Pina Vegas et al, 2022 ).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Given that the recommended maintenance dosing interval for ustekinumab is every 12 weeks (84 days), a 45-days gap may not be sufficient to assess discontinuation of ustekinumab. The study that used a 60-days treatment gap reported results that are consistent with our own; 1-year persistence in patients with psoriasis was 81.1% for ustekinumab versus 72.9% for adalimumab and 69.7% for etanercept ( Pina Vegas et al, 2022 ). Over the entire 3-years observation period ustekinumab was associated with higher persistence than all tumor necrosis factor inhibitors (HR 0.76, 95% CI 0.72–0.80) ( Pina Vegas et al, 2022 ).…”
Section: Discussionsupporting
confidence: 85%
“…The study that used a 60-days treatment gap reported results that are consistent with our own; 1-year persistence in patients with psoriasis was 81.1% for ustekinumab versus 72.9% for adalimumab and 69.7% for etanercept ( Pina Vegas et al, 2022 ). Over the entire 3-years observation period ustekinumab was associated with higher persistence than all tumor necrosis factor inhibitors (HR 0.76, 95% CI 0.72–0.80) ( Pina Vegas et al, 2022 ). Persistence was also substantially higher among ustekinumab users (70.8 versus 53.4% for adalimumab and 19.0% for etanercept) in the study that used a dose-defined treatment gap for each biologic ( Feldman et al, 2015 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This criterion can be considered a composite of efficacy (a treatment considered ineffective is likely to be discontinued) and safety (a poorly tolerated treatment is likely to be discontinued) but also of patient satisfaction or preference and adherence 14. Some studies have compared the persistence of biologics as first-line therapy in PsA,15–17 but although this is an important issue, limited data are available on persistence of second-line treatment in real life, particularly after TNFi discontinuation 18…”
Section: Introductionmentioning
confidence: 99%